Analysis of 7th Grade Students’ Inductive Reasoning Skill in PBL-Bertema Model Towards Responsibility Character - Istikomah, Fajar; Rochmad, Rochmad; Winarti, Endang Retno (Department of Mathematics, Universitas Negeri Semarang, 2017)
This study aims to (1) to test the PBLBertema effectiveness of students inductive reasoning abilities, (2) to analize students inductive reasoning abilities in terms of student responsibilities. This research is quantitative research followed by interview. The population is the class of VII SMP N 3 Ungaran as many as 343 students with the sample of the class students VII G as the experimental group of 35 students and the class students VII E as the control group of 33 students. The instrument used is a matter of inductive reasoning test, responsibility character questionnaire, student response questionnaire, and teacher activityobservation sheet. The data obtained were analyzed using proportion test, t-test, two propotion test, paired ttest, and normalized gain. The subjects of this reasearch are each of the two students with high responsibility, medium responsibility, and low responsibility. The results of this study indicated that PBLBertema learning is effective to improve students inductive reasoning abilities. Students with high responsibility are able to dominate all inductive reasoning indicators that is data ghatering, finding patterns, and making conclusions; Students with medium responsibility have not able to dominate indicator finding patterns; Students with low responsibility have not able to dominate indicator finding patterns and making conclusions.